(3TQM dGejI GdYLes - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s ((3MeRI Hf bGSe GdTgGHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOQ ef JCOH aEf GdbUjOI GdehSheI HdGejI GdYLe CeG aUGMI daXgG ajSHb GdSeY Edi MaXgG s
(3BNQgG (B:s
(3heG GJi HGdhGh ai UOYg GdG hbO QJH ai YWag hda ai GdHQO GYWGag MJi jWjH GdfTQ ai dag s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1537s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs